2010
DOI: 10.4314/jasem.v12i3.55497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lead and cadmium on germination and seedling growth of <i>Leucaena leucocephala</i>

Abstract: ABSTRACT:A study was conducted to determine the effect of different concentrations of lead and cadmium on seed germination and seedling growth of Leucaena leucocephala. Seed were grown under laboratory conditions at 25, 50, 75 and 100 ppm of metal ions of lead and cadmium. Both lead and cadmium treatments showed toxic effects on various growth indices of L. leucocephala. Increasing the concentration of lead to 75 ppm, significantly (p<0.05) decreased seed germination as compared to control. Seedling and root g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 13 publications
(8 reference statements)
9
42
1
1
Order By: Relevance
“…A possible explanation could be ascribed to the reduction in mitotic cells of the root meristematic zone. A similar phenomenon was observed in a previous study on the effect of lead and cadmium on the growth of Leucaena leucocephala seedlings [38]. At 10 mM, seedling growth was severely retarded and short browning roots were observed in Pb and Zn treatments.…”
Section: Discussionsupporting
confidence: 89%
“…A possible explanation could be ascribed to the reduction in mitotic cells of the root meristematic zone. A similar phenomenon was observed in a previous study on the effect of lead and cadmium on the growth of Leucaena leucocephala seedlings [38]. At 10 mM, seedling growth was severely retarded and short browning roots were observed in Pb and Zn treatments.…”
Section: Discussionsupporting
confidence: 89%
“…The results showed that the Cd was found to be the most toxic metal for wheat crop. This was also found in wheat and other species by other authors (Mathur et al, 1987;Iqbal, Mehmood, 1991;Shafiq et al, 2008;Moosavi et al, 2012;Shaikh et al, 2013). Regarding Iron, root and shoot length of wheat decreased significantly at the highest concentrations of Iron, when compared with the control.…”
Section: Discussionsupporting
confidence: 80%
“…Some previous studies have proved that higher Cd levels imposed adverse effect on seed germination resulted in retarded plant growth (Shafiq et al, 2008;Aydinalp and Marinova, 2009;Zhang et al, 2012) as in alfalfa seeds (Peralta et al, 2001). Cd interference changes the permeability of cell membrane which lessened absorption and transport of water as well as reduced the stress tolerance potential during germination (Russak et al, 2008).…”
Section: Discussionmentioning
confidence: 99%